Association between socioeconomic and psychological experiences of parents with children on Leukemia treatment in Kenyatta National Hospital, Kenya - Roselyne Anyango Okumu; Margret Muiva; Miriam Wagoro; Fatmah Abdallah; Erick Oweya (Elsevier, 2017)
Objective: The survival rate for children with leukemia has increased dramatically since the late 1990s; treatment effects of the disease can be extremely stressful for families. Research on psychological and socioeconomic effects of leukemia treatment had been conducted in Western countries, but little is known within Africa including Kenya. Methods: This was a cross-sectional study with a sample of 62 out of 72 parents of children undergoing leukemia treatment at Kenyatta National Hospital. Data were collected between May and August 2015 using structured questionnaires while qualitative data were collected using focus group discussions. This manuscript is based on quantitative data which were entered into EpiData version 3.1 and analyzed using SPSS version 20. Psychological distress index was created by counting the number of psychological experiences reported by respondents. Kendall's tau-b was used to test the association between the psychological distress index and socioeconomic characteristics; P ≤ 0.05 was considered statistically significant. Results: The respondents experienced anxiety, shock, and fatigue. Spending a higher proportion of family's income was associated with higher psychological distress index (P = 0.009). The economic challenge led to significantly heightened tension in the family (P = 0.021). Conclusions: Financial challenge is a major cause of psychological distress thus needs for financial support through collaboration with government institutions, for example, NHIF, development agencies, and nongovernment organization who can contribute toward the treatment cost. Need to decentralize effective leukemia treatment centers. Psychological support and counseling should be done to alleviate tension. The nurse needs to be empathetic when caring for the child and family as well as to apply the ethical principles of justice and beneficence so that the child gets the best care despite the financial challenge.